Research of Automation Equipment for Evaporation in Vacuum - Saliyeva Olima Kamalovna; Elmuradova Guzal (Research Parks Publishing LLC, 2021)
This Article Examines The Means of Automating Evaporation in a Vacuum. The Classification of Modern Microprocessor Software and Hardware Systems Used in The Evaporation Process is Considered.